Fluktuasi Nilai Fosfat dan Nitrat pada Pembesaran Ikan Nila dengan Sistem Aquaponik yang Diberi Tanaman Mint (Mentha arvensis) - Kurniawan, Made Sandi; Arthana, I Wayan; Kartika, Gde Raka Angga (Current Trends in Aquatic Science; Vol 6 No 1 (2023), 2023)
Nitrate and phosphate enrichment in Tilapia culture can be minimized using the concept of aquaponics by growing aquatic plants around the cultivation area. The purpose of this study was to determine fluctuations in phosphate and nitrate values ??in tilapia rearing using aquaponics technology using mint (M. arvensis) plants. B, and the three plants sink beyond the roots to the stem (C).  The method that use in research is eksperiment with Random Project Complete (RAL). After a month, the highest average growth rate of mint (M arvensis) occurred in treatment A and the lowest in treatment C. The highest specific growth was in treatment A and the lowest was in treatment B. The highest survival rate was in treatment C and the lowest was in treatment B. The best phosphate absorption was found in treatment B with a decrease of 0,12 mg/L, and the lowest was in treatment C with a value of 0,08 mg/L. The best nitrate absorption was found in treatment A with a decrease of 1,38 mg/L, and the lowest in treatment C with an increase of 0,69 mg/L. The results of the One-Way ANOVA statistical test with Duncan's follow-up test showed significantly different treatments for phosphate and nitrate measurements.